Composite energy storage material and preparation method and refrigeration method thereof
By pressing amorphous n-alkanes into the graphene-carbon nanoframe structure, efficient refrigeration is achieved by using structural deformation, the problems of leakage, efficiency and thermal conductivity in the alkane refrigeration technology are solved, and low energy consumption and high efficiency refrigeration are achieved.
Patent Information
- Application Number
- CN202411258022.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing alkane refrigeration technology has problems such as high leakage risk, low refrigeration efficiency, low thermal conductivity and large volume changes, which limits its application in the refrigeration field.
The graphene-carbon nanoframe is used to press the amorphous n-alkanes into it, absorb or release heat through structural deformation, and achieve efficient refrigeration, and the strong covalent bonds of the graphene frame improve thermal conductivity.
The uniaxial compression stress is reduced, the thermal conductivity is improved, the refrigeration efficiency is enhanced, the material fatigue is avoided, and the heat exchange speed is improved.
Smart Images

Figure CN119119974A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of refrigeration technology, and in particular to a composite energy storage material and a preparation method thereof, and a refrigeration method. Background Art
[0002] Alkane refrigeration technology is a new type of refrigeration technology. It uses normal alkanes (the main chemical component of paraffin) to achieve refrigeration effect through phase change from liquid to solid under a certain pressure. This technology has the advantages of being green, low cost, stable physical and chemical properties, and the phase change process does not produce harmful emissions, which is convenient for the miniaturization of refrigeration equipment. Therefore, it has broad application prospects in the field of refrigeration. Existing refrigeration equipment mainly adopts gas compression cycle technology to achieve refrigeration effect through refrigerants, but this method has high energy consumption. In contrast, solid and liquid are two common forms of matter, and their mutual transformation is accompanied by thermal response, such as heat release and heat absorption from the surrounding environment when water drops into ice and ice melts into water. In solid phase change materials, thermal response will occur rapidly when driven by external fields such as magnetic field, electric field, uniaxial pressure and net water pressure, that is, solid phase change thermal effect, which can be used for refrigeration. However, the refrigeration performance of existing solid phase change refrigeration materials is difficult to match that of traditional gas refrigerants, which limits their practical application.
[0003] Although alkane refrigeration technology has the advantages of being environmentally friendly and efficient, it also has some disadvantages and limitations: High risk of leakage: Due to the flammability of alkane refrigerants, once a leak occurs, they may mix with air to form flammable gases, increasing safety risks. Low refrigeration efficiency: Although alkane refrigerants have some energy-saving advantages, their refrigeration efficiency may not be as good as other types of refrigerants in some applications. Low thermal conductivity: The thermal conductivity of alkanes is relatively low, which means that they are not efficient in heat transfer during heat absorption and heat release, which may limit their use in applications that require rapid heat exchange. Large volume change: During the phase change process, alkanes may undergo large volume changes, which may cause structural instability of the material in long-term use and may even damage the heat storage system. Summary of the invention
[0004] In order to solve the technical problems existing in the above-mentioned existing alkane refrigeration technology, the present invention provides a composite energy storage material and its preparation method and refrigeration method. The present invention presses amorphous normal alkanes into graphene-carbon nanoframes. The "soft" characteristics of graphene-carbon nanoframes and amorphous normal alkanes are relatively easy to be compressed, so the driving force is small, especially compared with the uniaxial stress required by the same type of spring-stuck materials, which is one order of magnitude smaller. Under the action of stress, the structure of amorphous normal alkanes is easily deformed, so the configuration entropy will change greatly, thereby absorbing or releasing a large amount of heat, achieving the effect of heat storage and heat release.
[0005] To achieve the above object, the present invention provides a method for preparing a composite energy storage material, comprising the following steps:
[0006] Step 1: combining graphene and carbon nanotubes into a graphene framework structure at room temperature;
[0007] Step 2: Raise the temperature from room temperature to 290K-320K to convert the solid n-alkane C n H 2n+2 Melted liquid state; wherein 16≤n≤20, n is an integer;
[0008] Step 3: liquid normal alkane C obtained in step 2 n H 2n+2 The composite material is then pressed into the graphene frame obtained in step 1 and packaged to obtain the composite material. The temperature of the composite material is maintained above 300K to make the liquid n-alkane C n H 2n+2 Without solidification, the composite energy storage material is obtained.
[0009] Furthermore, in step 1, the ratio of graphene to carbon nanotubes is 3 to 4:1.
[0010] Further, in step 2, the liquid normal alkane C n H 2n+2 The density is 0.6~0.8g·cm -3 .
[0011] Further, in step 3, the liquid normal alkane C n H 2n+2 The mass ratio of the graphene framework is 1 to 2:1.
[0012] The present invention also provides a composite energy storage material, which is prepared by the above-mentioned preparation method.
[0013] Furthermore, the thermal conductivity of the composite energy storage material reaches 4W·m -1 ·K -1 above.
[0014] Furthermore, the maximum input stress of the composite energy storage material is lower than 80 MPa, and the maximum adiabatic temperature change reaches 20K.
[0015] The present invention also provides a refrigeration method, comprising the following steps:
[0016] First, the composite energy storage material is adiabatically compressed along the Z-axis direction, and the temperature of the composite energy storage material is reduced;
[0017] The compressed composite energy storage material is then heat-exchanged with the indoor environment to absorb heat from the indoor environment;
[0018] Then, the composite energy storage material is subjected to adiabatic stretching, and the temperature of the composite energy storage material is increased;
[0019] Finally, the composite energy storage material is heat exchanged with the external environment to output heat to the external environment.
[0020] Furthermore, the composite energy storage material is adiabatically compressed along the Z-axis direction, and the compression strain rate adopted is 15% to 25%.
[0021] The present invention has the following beneficial effects:
[0022] 1. The present invention provides a method for preparing a composite energy storage material. Specifically, at room temperature, graphene and carbon nanotubes are first combined into a graphene framework structure; then the temperature is raised from room temperature to 290K-320K to convert solid normal alkane C n H 2n+2 Melt liquid; wherein, 16≤n≤20, n is an integer; finally, liquid normal alkane C n H 2n+2 The composite material is then pressed into the graphene frame and packaged to obtain the composite material. The temperature of the composite material is maintained above 300K to make the liquid n-alkane C n H 2n+2 The composite energy storage material is obtained without solidification. The thermal conductivity of the composite energy storage material obtained by the present invention reaches 4W·m -1 ·K -1 As mentioned above, the composite energy storage material can produce an adiabatic temperature change of about 22.5K at about 70MPa.
[0023] Because liquid n-alkanes are compressible, when subjected to external pressure, not only will the spatial position of n-alkanes change, but also their own configuration will change. Therefore, the changes in the various states of alkanes will bring about huge entropy changes (more than 300 J·Kg-1·K-1), and their own temperature will also increase or decrease (temperature change reaches about 22K), thereby exchanging heat with the outside world to achieve the purpose of refrigeration. In addition, liquid alkanes are amorphous and can be transformed into various forms, which can avoid the problem of material fatigue caused by high-frequency repeated compression.
[0024] The graphene-carbon nanotube framework structure has a good balance of rigidity and flexibility. Rigidity is that the interaction between atoms inside the graphene framework is a strong covalent bond, so it is not easy to break and has good structural stability. In addition, this strong interaction is conducive to rapid heat conduction, thereby greatly increasing the thermal conductivity of the system. Softness is achieved through the staggered distribution of carbon nanotubes on the graphene sheet. When the framework is subjected to uniaxial stress, the internal carbon nanotubes do not repel each other, and the graphene sheet produces a large wrinkle deformation. In this way, the graphene framework structure can be changed from the spatial structure without requiring large external input stress. Changes in the graphene framework structure will lead to changes in the state quantity of liquid alkanes.
[0025] The "soft" properties of graphene-carbon nanoframes and amorphous n-alkanes make them easier to compress, so the driving force is smaller, especially compared to the uniaxial stress required by the same type of spring-loaded materials, which is one order of magnitude smaller. Amorphous n-alkanes are prone to structural deformation under stress, so the configuration entropy will change greatly, which will absorb or release a large amount of heat, achieving the effect of heat storage and heat release. Due to the characteristics of strong covalent bonds, the thermal conductivity of graphene-carbon nanoframes can reach 4W·m -1 ·K -1 The above can achieve the effect of heat transfer.
[0026] 2. The stress required for the spring-cage effect refrigeration of traditional nickel-titanium alloy (NiTi) is more than 400GPa. The energy storage composite material prepared by the present invention can reduce the uniaxial compressive stress input from the outside, that is, reduce energy consumption. The uniaxial compressive stress can be as low as about 70MPa, which greatly saves energy consumption. At the same time, the thermal conductivity is high, because the present invention introduces CNT into graphene to form a three-dimensional network structure, increase the contact area, and thus improve the thermal conductivity of the composite material, and increase the thermal conductivity of the alkane-graphene framework composite material by more than an order of magnitude. Although the original alkane can be used for refrigeration, its thermal conductivity is very low, as low as 0.2W·m -1 ·K -1 , which seriously affects the heat exchange rate and limits its application. The thermal conductivity of the energy storage composite material prepared by the present invention can reach 4W·m -1 ·K -1 , greatly improved by an order of magnitude. And the graphene framework can encapsulate liquid amorphous n-alkanes to prevent leakage. In addition, the driving stress of the NiTi alloy card effect refrigeration must reach more than 400MPa to drive a temperature change of about 20K. In comparison, the synthesized energy storage composite material of the present invention can produce an adiabatic temperature change of about 22.5K at about 70MPa, which has a great energy-saving advantage. Because when the graphene-carbon nanoframe and amorphous C 17 H 36When the alkane is squeezed under adiabatic conditions, its own temperature will drop by 22K, resulting in a temperature difference with the indoor environment, absorbing heat from the indoor environment. Moreover, after squeezing, when the graphene-carbon nanoframe and amorphous alkane are stretched back under adiabatic conditions, their own temperature will rise, higher than the heat of the external environment, thus transferring heat to the external environment.
[0027] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0029] Figure 1 The present invention provides a method for synthesizing a composite energy storage material; wherein, Figure 1 (a) is a graphene framework; (b) is a liquid alkane CnH 2n+2 ; (c) is a composite energy storage material made of graphene framework and liquid alkane.
[0030] Figure 2 is a schematic diagram of the structure of a preferred embodiment of the present invention; wherein, Figure 2 (a) shows the initial state of the composite material of graphene framework and liquid alkane; (b) shows the structure of the composite material after being compressed by pressure; (c) shows the structure of the composite material after being compressed by pressure. 17 H 36 Temperature variation of liquid alkane composite material during stretching and compression under adiabatic conditions.
[0031] Figure 3 is a performance comparison chart of different variables of the present invention; wherein, Figure 3 (a) shows the relationship between the cooling effect (adiabatic temperature change) and the number of carbon chains; (b) shows the relationship between C 17 H 36 Relationship between alkane density and external applied stress; (c) C 17 H 36 The density of alkanes is 0.7 g·cm - 3 cases, CNT-Gra / C 17 H 36 (d) is a graph showing the relationship between applied stress and compression rate of the composite material; (d) is a graph showing the thermal conductivity comparison of different structures.
[0032] Figure 4 It is the CNT-Gra / C of the preferred embodiment of the present invention. n H 2n+2Refrigeration performance diagram of composite materials; where, Figure 4 (a) CNT-Gra / C at room temperature 300K and 20% compressive strain n H 2n+2 Comparison of the cooling effect (adiabatic temperature change (△T), thermal efficiency (△T / △σ)) of the composite material and other classic solid-state cooling materials (including elastic card materials (eC) and compression card materials (BC)); (b) CNT-Gra / C 17 H 36 (0.7 g cm - 3) Comparison chart of thermal conductivity (κ), isothermal entropy change (△S), adiabatic temperature change (△T), thermal efficiency (△T / △σ) and phase change temperature point (T) of classic compression card material neopentyl glycol (NPG for short) and classic spring card material nickel titanium (NiTi for short). DETAILED DESCRIPTION
[0033] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.
[0034] Embodiment 1:
[0035] A method for preparing a composite energy storage material comprises the following steps:
[0036] Step 1: Figure 1 As shown in (a), at room temperature, graphene and carbon nanotubes form a graphene framework structure (CNT-Gra). The carbon nanotubes are (3,3) type, and the connection between carbon nanotubes and graphene is a covalent bond. This graphene framework structure has been synthesized experimentally and has been widely used, so it is reasonable for us to use this structure.
[0037] Step 2: Figure 1 As shown in (b), the temperature is raised from room temperature to 320K, and the solid n-heptadecane (C 17 H 36 ) melts into liquid state and maintains a liquid density of 0.70 g·cm -3 This density is in the order of magnitude of 0.77 g cm -3 The difference is almost the same, and it can be easily controlled by introducing impurities or increasing the temperature.
[0038] Step 3: Figure 1 As shown in (c), liquid n-heptadecane (C 17 H 36 ) is composited with the graphene framework structure. Liquid C with a density of 0.70 g·cm-3 17 H 36The composite material is then pressed into the graphene frame and packaged, and the temperature of the composite material is maintained above 300K to keep the liquid C 17 H 36 It will not solidify. 17 H 36 ) can exist in the graphene framework in a liquid state, that is, CNT-Gra / C 17 H 36 Composite energy storage materials.
[0039] The method for refrigeration using the composite energy storage material is as follows:
[0040] 1) First, the concentration of 0.7 g cm -3 C 17 The alkane of H36 is combined with the graphene-carbon nanotube framework to form the composite material CNT-Gra / C 17 H 36 (0.7 g cm -3 ),like Figure 1 As shown in (c).
[0041] 2) Then the composite material CNT-Gra / C 17 H 36 (0.7 g cm -3 ) is adiabatically compressed along the Z-axis with a compression strain rate of 20%. Figure 2 (a) to Figure 2 As shown in (b). In this process, CNT-Gra / C 17 H 36 (0.7 g cm -3 )The temperature of the composite material itself dropped by about 20K.
[0042] 3) Then the compressed CNT-Gra / C 17 H 36 (0.7 g cm -3 )The composite material exchanges heat with the indoor environment, absorbs heat from the indoor environment, and the composite material returns to 300K.
[0043] 4) Then CNT-Gra / C 17 H 36 (0.7 g cm -3 )The composite material undergoes adiabatic stretching, and its temperature rises by about 10K.
[0044] 5) Finally, the composite material exchanges heat with the external environment and outputs heat to the external environment. The specific temperature change diagram of the composite material itself is as follows: Figure 2 As shown in (c).
[0045] The composite material CNT-Gra / C is completed through steps 1) to 5). 17 H 36 (0.7 g cm -3 ) refrigeration process. In this process, the maximum input stress is less than 80MPa, the maximum adiabatic temperature change reaches 20K, and the thermal conductivity is about 12W·m-1·K -1 Around, refrigeration is better than most other refrigeration materials.
[0046] Embodiment 2:
[0047] A method for preparing a composite energy storage material, characterized in that it comprises the following steps:
[0048] Step 1: combining graphene and carbon nanotubes into a graphene framework structure at room temperature;
[0049] Step 2: Raise the temperature from room temperature to 290K-310K to convert the solid n-alkane C 16 H 34 Melted liquid state; wherein n is 16;
[0050] Step 3: liquid normal alkane C obtained in step 2 16 H 34 The composite material is pressed into the graphene frame obtained in step 1 and packaged to obtain the composite material, and the temperature of the composite material is maintained above 300K so that the liquid normal alkane does not solidify, thereby obtaining the composite energy storage material.
[0051] The specific refrigeration method is the same as that in Example 1.
[0052] Embodiment 3:
[0053] A method for preparing a composite energy storage material, characterized in that it comprises the following steps:
[0054] Step 1: combining graphene and carbon nanotubes into a graphene framework structure at room temperature;
[0055] Step 2: Raise the temperature from room temperature to 290K-320K to convert the solid n-alkane C 40 H 42 Melted liquid state; wherein n is 20;
[0056] Step 3: liquid normal alkane C obtained in step 2 20 H 42 The composite material is pressed into the graphene frame obtained in step 1 and packaged to obtain the composite material, and the temperature of the composite material is maintained above 300K so that the liquid normal alkane does not solidify, thereby obtaining the composite energy storage material.
[0057] The specific refrigeration method is the same as that in Example 1.
[0058] Comparative Example 1: (n is too small, the carbon chain length is too short)
[0059] The difference between Comparative Example 1 and Example 1 is that the normal alkane is C9H 20 , other steps are the same as in Example 1.
[0060] Comparative Example 2: (n is too large, the carbon chain length is too long)
[0061] The difference between Comparative Example 2 and Example 1 is that the normal alkane is C 21 H 44 , other steps are the same as in Example 1.
[0062] Comparative Example 3: (Alkane density is too small)
[0063] The difference between Comparative Example 3 and Example 1 is that the density of n-heptadecane is 0.4 g·cm -3 , other steps are the same as in Example 1.
[0064] Comparative Example 4: (Alkane density is too high)
[0065] The difference between Comparative Example 4 and Example 1 is that the density of n-heptadecane is 0.9 g·cm -3 , other steps are the same as in Example 1.
[0066] Comparative Example 5: (Compression strain rate is too small)
[0067] The difference between Comparative Example 5 and Example 1 is that the compression strain rate during the refrigeration process is 10%, and the other steps are the same as Example 1.
[0068] Comparative Example 6: (Compression strain rate is too high)
[0069] The difference between Comparative Example 6 and Example 1 is that the compression strain rate during the refrigeration process is 30%, and the other steps are the same as Example 1.
[0070] Figure 2 (a) and Figure 2 (b) respectively describes the CNT-Gra / C under uniaxial compressive strain along the Z-axis at room temperature and pressure. 17 H 36 The state of the composite material. Figure 2 In (a), it can be observed that the alkanes are randomly distributed in the gaps between the graphene layers. Due to the compressive strain along the Z-axis, the alkane molecules are compressed between the graphene layers, resulting in a more compact structure, making the graphene layers present a wrinkled structure. 17 H 36 Reverse spring-card effect of composite materials. Figure 2 (c) shows that under 20% compressive strain, CNT-Gra / C17 H 36 (0.7 g cm -3 ) Adiabatic temperature change diagram of the composite material. Initially, the composite material was thermally balanced for 1 ns (nanoseconds) at an atmospheric pressure and a temperature of 300K. Subsequently, from 1 ns to 3 ns, a compressive strain was adiabatically applied along the Z-axis direction, and the strain was gradually increased to 20%, so that the stress in the Z direction of the composite material reached 135 MPa, causing its own temperature to drop by 14K. Then from 3 ns to 4 ns, the composite material was thermally balanced in the NVE (conservation of number, volume and energy) ensemble. Then from 4 ns to 6 ns, the composite material was placed in a 300K environment with constant external stress, and heat exchanged with the outside world, so that the temperature quickly returned to the original 300K. Then from 6 ns to 8 ns, the compressive strain was released in adiabatically with the outside world, so that the composite material gradually returned to the initial state. This measure caused the temperature of the system to increase by 13K. Then, the thermal equilibrium of the NVE ensemble was carried out from 8 ns to 9 ns. Finally, the composite material was placed in a 300K environment for a 1 ns heat exchange, so that the temperature of the system gradually returned to 300K. Therefore, the composite material CNT-Gra / C 17 H 36 (0.7 g cm -3 ) exhibits an adiabatic temperature change of 22.5K under a uniaxial stress of only about 75MPa, with a cooling efficiency significantly higher than that of most traditional snap-action materials. In addition, the adiabatic temperature change increases with the carbon number, but the stress required is smaller.
[0071] Amorphous C n H 2n+2 The interaction force between molecules is the van der Waals force. n H 2n+2 It exists in gaseous, liquid or solid form at room temperature, depending on the length of the carbon chain in the alkane (the more carbon atoms, the higher the melting point). Figure 1 (c) represents amorphous C n H 2n+2 molecules and carbon nanotube-graphene framework (CNT-Graphene) composites, in which amorphous C n H 2n+2 The molecular weight is 0.6~0.7g·cm -3 The density of C is randomly distributed within the frame. n H 2n+2 The higher the concentration of molecules, the higher the CNT-Gra / C n H 2n+2 The higher the mass density, specific heat capacity and heat absorption of the composite material.
[0072] like Figure 3(a) shows that the -3 As an example, under a compressive stress of less than 150MPa, different CNT-Gra / C n H 2n+2 The maximum compression ratio of the composite material and the corresponding adiabatic temperature change (ΔT) both show a linear growth trend and increase with the increase of carbon chain length (n). Low adiabatic temperature change is defined as ΔT below 13K and high adiabatic temperature change is ΔT greater than 15K. Figure 3 As shown in (a), when the carbon chain number is less than 15 (such as in Comparative Example 1, when the normal alkane is C9H 20 ), the alkane is in a gaseous state, which is easy to compress, but the adiabatic temperature change is small, and the refrigeration effect is not good. When the carbon chain number is between 16 and 20 (such as Examples 1-3), the alkane is in a liquid state, which is easy to compress, and the adiabatic temperature change can reach 20K, and the refrigeration effect is significant. When the carbon chain number exceeds 20 (such as the normal alkane selected in Comparative Example 2 C 21 H 44 ), alkanes are solid and not easily compressed. Therefore, when the carbon chain number is in the range of 16 to 20, it provides the best refrigeration effect.
[0073] Figure 3 (b) shows the compression strain of 20%, C 17 H 36 The relationship between the density of alkanes and the external applied stress. Figure 3 From (b), we can see that at room temperature, when the density of alkanes is lower than 0.6 g·cm -3 When the applied stress is small (such as in Comparative Example 3), the adiabatic temperature change is also small, and the refrigeration effect is poor. -3 When the applied stress is less than 100 MPa (such as in Examples 1-3), the adiabatic temperature change can reach above 18K, and the refrigeration effect is optimal. -3 When the applied stress increases rapidly (such as in Comparative Example 4), it exceeds 300 MPa, which does not meet the energy-saving requirements. Therefore, we chose an alkane with a density of 0.7 g·cm -3 .
[0074] Figure 3 (c) is C 17 H 36 The density of alkanes is 0.7 g·cm - 3 cases, CNT-Gra / C 17 H 36 Plot of applied stress versus compression for a composite material. Figure 3As shown in (c), when the compression rate is less than 15% (such as comparative example 5), the applied stress is less than 100 MPa, and the energy saving effect is significant. When the compression rate exceeds 25% (such as comparative example 6), the stress increases rapidly to more than 200 MPa, and the energy consumption is high. When the compression strain rate is 15% to 25%, the energy saving and efficiency are the highest.
[0075] Figure 3 (d) is a comparison of the thermal conductivity of alkanes with different carbon chain numbers at different concentrations and directions. Figure 3 As shown in (d), no matter how the carbon chain number and concentration change, the thermal conductivity of pure alkanes is very low, less than 1 W·m -1 ·K -1 However, when alkanes are combined with carbon nanotube-graphene frameworks, the thermal conductivity is significantly improved, reaching 4 W·m along the Z direction. -1 ·K -1 , along the XY plane direction can reach 10W·m -1 ·K -1 This shows that CNT-Gra / C 17 H 36 The composite material has excellent thermal conductivity.
[0076] Based on the comprehensive consideration of carbon chain number, alkane concentration, compression strain rate and thermal conductivity, CNT-Gra / C 17 H 36 (0.7g·cm-3) The composite material can achieve the best effect, ensuring the refrigeration effect and energy saving efficiency.
[0077] Figure 4 (a) and Figure 4 (b) shows the CNT / C at room temperature 300K and 20% compressive strain. n H 2n+2 The isothermal entropy change (ΔS), adiabatic temperature change (ΔT), and thermal efficiency (ΔT / Δσ) of the composite material are compared with other classic solid-state refrigeration materials (including elastic card materials (eC) and compression card materials (BC)). It can be observed that although CNT-Gra / C 17 H 36 The composite material has a ΔT lower than some alloy materials (such as NiTi) and a ΔS lower than some plastic crystal materials (such as NPG), but its ΔT is about 20K and ΔS is about 200J·kg-1·K-1, and its refrigeration performance is also excellent compared with other solid refrigeration materials. Most importantly, its refrigeration efficiency ΔT / Δσ, ΔS / Δσ and thermal conductivity are very high, which is mainly due to the flexibility and high thermal conductivity of CNT-Gra, as well as the amorphous C n H 2n+2 The complexity of the structural changes of CNT-Gra and Cn H 2n+2 Flexibility of CNT-Gra / C 17 H 36 (0.7 g·cm-3) can achieve excellent refrigeration performance at a relatively low uniaxial driving pressure (~70 MPa). Compared with other mechanical card effect refrigeration materials, CNT-Gra / C 17 H 36 (0.7g·cm-3) Composite materials are more energy-efficient.
[0078] From the above, we can see that the refrigeration effect should be good, that is, the adiabatic temperature change (△T) should be as large as possible; the input work should be small, that is, the input stress (Stress) should be as small as possible to achieve the purpose of energy saving and environmental protection; the thermal conductivity (κ) should be as high as possible. Therefore, by comprehensively comparing different alkane concentrations, different compression amplitudes, and different carbon chain lengths, the composite material with the best comprehensive performance is selected.
[0079] In summary, the present invention provides a method for preparing a composite energy storage material. Specifically, at room temperature, graphene and carbon nanotubes are first combined into a graphene framework structure; then the temperature is raised from room temperature to 290K-320K to convert solid normal alkane C n H 2n+2 Melt liquid; wherein, 16≤n≤20, n is an integer; finally, liquid normal alkane C n H 2n+2 The composite material is then pressed into the graphene frame and packaged to obtain the composite material. The temperature of the composite material is maintained above 300K to make the liquid n-alkane C n H 2n+2 The composite energy storage material is obtained without solidification. The thermal conductivity of the composite energy storage material obtained by the present invention reaches 4W·m -1 ·K -1 As mentioned above, the composite energy storage material can produce an adiabatic temperature change of about 22.5K at about 70MPa.
[0080] Because liquid n-alkanes are compressible, when subjected to external pressure, not only will the spatial position of n-alkanes change, but their own configuration will also change. Therefore, the changes in the various states of alkanes bring about huge entropy changes (300 J·Kg -1 ·K -1 Above), its own temperature will also rise or fall (temperature change reaches about 22K), thereby exchanging heat with the outside world to achieve the purpose of refrigeration. In addition, liquid alkanes have the characteristics of amorphousness and can be transformed into various forms, which can avoid the material fatigue problem caused by high-frequency repeated compression.
[0081] The graphene-carbon nanotube framework structure has a good balance of rigidity and flexibility. Rigidity is that the interaction between atoms inside the graphene framework is a strong covalent bond, so it is not easy to break and has good structural stability. In addition, this strong interaction is conducive to rapid heat conduction, thereby greatly increasing the thermal conductivity of the system. Softness is achieved through the staggered distribution of carbon nanotubes on the graphene sheet. When the framework is subjected to uniaxial stress, the internal carbon nanotubes do not repel each other, and the graphene sheet produces a large wrinkle deformation. In this way, the graphene framework structure can be changed from the spatial structure without requiring large external input stress. Changes in the graphene framework structure will lead to changes in the state quantity of liquid alkanes.
[0082] The "soft" properties of graphene-carbon nanoframes and amorphous n-alkanes make them easier to compress, so the driving force is smaller, especially compared to the uniaxial stress required by the same type of spring-loaded materials, which is one order of magnitude smaller. Amorphous n-alkanes are prone to structural deformation under stress, so the configuration entropy will change greatly, which will absorb or release a large amount of heat, achieving the effect of heat storage and heat release. Due to the characteristics of strong covalent bonds, the thermal conductivity of graphene-carbon nanoframes can reach 4W·m -1 ·K -1 The above can achieve the effect of heat transfer.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite energy storage material, characterized in that: The following steps are involved: Step 1: combining graphene and carbon nanotubes into a graphene framework structure at room temperature; Step 2: Raise the temperature from room temperature to 290K-320K to convert the solid n-alkane C n H 2n+2 Melted liquid state; wherein 16≤n≤20, n is an integer; Step 3: liquid normal alkane C obtained in step 2 n H 2n+2 The composite material is then pressed into the graphene frame obtained in step 1 and packaged to obtain the composite material. The temperature of the composite material is maintained above 300K to make the liquid n-alkane C n H 2n+2 Without solidification, the composite energy storage material is obtained.
2. The method for preparing a composite energy storage material according to claim 1, characterized in that: In step 1, the usage ratio of graphene and carbon nanotubes is 3 to 4:
1.
3. The method for preparing a composite energy storage material according to claim 1, characterized in that: In step 2, liquid n-alkane C n H 2n+2 The density is 0.6~0.8g·cm -3 .
4. The method for preparing a composite energy storage material according to claim 1, characterized in that: In step 3, liquid n-alkane C n H 2n+2 The mass ratio of the graphene framework is 1 to 2:
1.
5. A composite energy storage material, characterized in that: The method is prepared by the method according to any one of claims 1 to 5.
6. A composite energy storage material according to claim 5, characterized in that: The thermal conductivity of the composite energy storage material reaches 4 W·m -1 ·K -1 above.
7. A composite energy storage material according to claim 5, characterized in that: The maximum input stress of the composite energy storage material is lower than 80MPa, and the maximum adiabatic temperature change reaches 20K.
8. A refrigeration method, characterized in that: The following steps are involved: First, adiabatically compress the composite energy storage material according to any one of claims 5 to 7 along the Z-axis direction, so that the temperature of the composite energy storage material decreases; The compressed composite energy storage material is then heat-exchanged with the indoor environment to absorb heat from the indoor environment; Then, the composite energy storage material is subjected to adiabatic stretching, and the temperature of the composite energy storage material is increased; Finally, the composite energy storage material is heat exchanged with the external environment to output heat to the external environment.
9. The method for preparing a composite energy storage material according to claim 8, characterized in that: The composite energy storage material is adiabatically compressed along the Z-axis direction, and the compression strain rate used is 15% to 25%.
